System Shift in Indonesian Pharmaceutical Governance: From Administrative Licensing to a Regulated Health Operating System - Raymond Rubianto Tjandrawinata (Journal of Social Science (JoSS), 2026)
Indonesia’s recent health regulatory reforms reveal a significant transformation in the governance of pharmaceutical supply, health commodities, and risk-based business licensing. This article examines Minister of Health Regulation No. 5 of 2026 on Health Supplies and Minister of Health Regulation No. 11 of 2025 on Business Activity Standards and Product/Service Standards for Risk-Based Business Licensing in the Health Subsector. Rather than treating these instruments as isolated administrative regulations, the article argues that they represent a broader system shift: a transition from fragmented, document-based, and reactive health-sector regulation toward an integrated, anticipatory, risk-based, and digitally mediated regulatory architecture. Using doctrinal legal analysis, qualitative regulatory systems analysis, and the System Shift framework, the article analyzes how the Indonesian regulatory state seeks to connect needs planning, domestic production, import governance, technology transfer, buffer stocks, distribution, electronic procurement, business licensing, digital reporting, inspection, and administrative sanctions within a more coherent regulatory operating system. The findings suggest five major shifts: from product availability to supply resilience; from import dependence to conditional localization; from static licensing to risk-based authorization; from fragmented supervision to regulatory feedback loops; and from documentary compliance to operational compliance. The article concludes that Indonesia is moving toward what may be conceptualized as a regulated health operating system, although this transition presents challenges related to data reliability, interagency coordination, proportional enforcement, industrial readiness, and the balance between national resilience and access to innovation.